Persepsi Masyarakat Lokal Terhadap Pengembangan Hutan Mangrove Sebagai Kawasan Ekowisata Di Kampung Ruar Distrik Biak Timur Kabupaten Biak Numfor - Ferdinand Rumbino; Soetjipto Moeljono; Antoni Ungirwalu (Cassowary, 2021)
The mangrove forest area of ​​Kampung Ruar, East Biak District, is an area that has traditionally been a place for fishing and lime-making efforts by the community who have been hereditary. This condition raises questions from various parties whether this location is suitable to be developed as a mangrove ecotourism destination. Development of Mangrove Ecotourism by the Papua Provincial Forestry Service as a tourist attraction by utilizing local natural potential and supporting tourism policies in Biak Numfor Regency. This study aims to see the socio-cultural conditions of local communities in the Mangrove Forest Area of ​​Kampung Ruar, Biak Timur District, Biak Numfor Regency as an ecotourism area and to assess the local community's perceptions of the development of ecotourism areas in providing benefits to the community both economically and socio-culture in Kampung Ruar Distik Biak Regency. Timur Biak. The study hasli revealed that the perception of local communities about ecotourism (60%), community knowledge about resources (70%) and understanding of community knowledge about forest damage and aspects of forest protection are very good (67), most (49%) people who understand that the potential for ecotourism development has future prospects. The four alternative strategies for mangrove ecotourism in Kampung Ruar, Biak Timur District, Biak Numfor District in Kampung Ruar are as follows: (a) Development of a Tour Package between Mangrove Ecotourism and TBTA Biak; (b) Increase Knowledge and Community Empowerment; (c) Mangrove Rehabilitation and Community Empowerment; and (d) Mentoring and involvement of local communities in management.